2019
DOI: 10.1530/ec-19-0442
|View full text |Cite
|
Sign up to set email alerts
|

Leptin induces cell migration and invasion in a FAK-Src-dependent manner in breast cancer cells

Abstract: Breast cancer is the most common invasive neoplasia, and the second leading cause of the cancer deaths in women worldwide. Mammary tumorigenesis is severely linked to obesity, one potential connection is leptin. Leptin is a hormone secreted by adipocytes, which contributes to the progression of breast cancer. Cell migration, metalloproteases secretion, and invasion are cellular processes associated with various stages of metastasis. These processes are regulated by the kinases FAK and Src. In this study, we ut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 60 publications
1
49
1
1
Order By: Relevance
“…Recently, Juárez-Cruz et al hypothesized that leptin promotes FAK and Src activation in breast cancer cells and induces cell migration, metalloproteases secretion (MMP2 and MMP9), and invasion. They suggested that leptin is associated with the establishment of a more aggressive phenotype of cancer cells that leads to local invasion and to the formation of metastases [73].…”
Section: Leptin and Bone Metastasismentioning
confidence: 99%
“…Recently, Juárez-Cruz et al hypothesized that leptin promotes FAK and Src activation in breast cancer cells and induces cell migration, metalloproteases secretion (MMP2 and MMP9), and invasion. They suggested that leptin is associated with the establishment of a more aggressive phenotype of cancer cells that leads to local invasion and to the formation of metastases [73].…”
Section: Leptin and Bone Metastasismentioning
confidence: 99%
“…Notably, compared to four individual prognosis-associated genes, the combined gene signature panel had better discrimination performance in COAD patients. LEP was reported to promote cancer cell migration and invasion (25,26). DLX2 was indicated to increase the risk of metastasis in prostate cancer patients with a high expression of Ki67 (27).…”
Section: Discussionmentioning
confidence: 99%
“…Cruz et al [137] observed in in vitro models that leptin also promotes the activation of focal adhesion kinase, DOI: 10.1159/000507055 thus contributing to cell-cell adhesion weakening and increasing the secretion of metalloproteases (MMP-2 and MMP-9) required for ECM remodeling and cell migration in TNBC cell lines. Another study has demonstrated that free fatty acids added to co-cultures of breast cancer cells and adipocytes were transferred to cancer cells, driving fatty acid metabolism, resulting in increased proliferation and cell migration [138].…”
Section: Cancer-associated Adipocytesmentioning
confidence: 99%
“…Pathobiology 2020;87:[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142] …”
unclassified